“God’s Most Stubborn Enemy:” Jonathan Edwards on Spiritual Pride and the Hope of a Humble Faith - Setran, David P. (Journal of spiritual formation & soul care, 2024)
Spiritual pride is a threat to all who take spiritual formation seriously, but it is often difficult to discern. Reflecting on this vice within the revivals of the First Great Awakening and in his own life, Jonathan Edwards (1703-1758) both diagnosed the symptoms of spiritual pride and addressed its potential cures. This article looks specifically at Edwards’s analysis of spiritual pride and his perspectives on the pathways to overcoming its power. In the end, Edwards proposed that Christians could pursue spiritual formation and yet remain humble if they would develop a new perspective of “comparative meanness” and develop new postures of “self-examination” and “glorying.” Edwards’s vision for a humble spiritual formation provides helpful insights both for locating spiritual pride in the Christian life and for severing its varied roots.